The Acute Effects of Exercise Intensity on Inhibitory Cognitive Control in Adolescents - Peruyero, Fernando; Zapata, Julio; Pastor, Diego; Cervelló, Eduardo (Frontiers in Psychology, 2017)
Adolescence is an important stage for brain maturation. There are many studies of exercise-cognition relations, but there is still a lack of knowledge about the impact of combining different intensities of exercise on adolescents’ cognitive responses. The main objective of this study was to analyze the effect of three physical education sessions (based on Zumba dance) of different intensities (no exercise, predominantly light intensity, and predominantly vigorous intensity) on the inhibition response (measured with the Stroop test) in adolescents. Forty-four adolescent students (age 16.39±0.68) completed a Stroop test before and after the three different physical education sessions. The results show that only the predominantly vigorous session represented a strong enough stimulus to increase cognitive inhibitory control. This means that the cognitive effect of exercise can be conditioned by exercise intensity and implies the need to control exercise intensity in physical educational programs for adolescents.